Sex differences in personality disorders in a Chinese clinical population - He, HongZhen; Xu, Mei; Fei, ZhangYing; Xie, Yuou; Gu, XinYi; Zhu, HongLiang; Wang, JunJie (Frontiers in Psychiatry, 2022)
Introduction: Sex differences in the frequency and severity of personality disorders (PDs) have been widely reported in Western countries. However, limited literature suggests a similar sex distribution in the Chinese clinical population. This study investigated sex differences in self-reported and interviewed patients with PDs in a clinical population in China. Materials and Methods: The participants were 1389 consecutive outpatients with a mean age of 30.5 years, including 634 (45.6%) males and 755 (54.4%) females. Self-reported PD traits were assessed using the Personality Diagnostic Questionnaire Fourth Edition Plus (PDQ-4+). PDs were diagnosed according to the Structured Clinical Interview for Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition (DSM-IV) Axis II (SCID-II). Results: Male outpatients reported more paranoid, schizotypal, antisocial, and passive-aggressive PD traits, whereas females reported more borderline PD traits on the PDQ-4+. Self-reported PD traits in male outpatients were more likely to reach the positive threshold of antisocial PD than in females (χ2=5.293, p=0.021). Males were more likely to meet the criteria for schizoid (χ2=5.050, p=0.025), narcissistic (χ2=27.244, p<0.001), antisocial (χ2=11.430, p=0.001), avoidant (χ2=5.098, p=0.024), and obsessive-compulsive PD (χ2=5.496, p=0.019) diagnoses in the SCID-II. In contrast, females were more likely to meet the criteria of histrionic (χ2=12.327, p=0.001), borderline (χ2=28.538, p<0.001), and dependent (χ2=4.919, p=0.027) diagnoses. Discussion: These findings indicate gender differences in the traits, frequency, and pattern of PDs when assessed in a Chinese clinical population.